The Influence of Emotion on Fairness-Related Decision Making: A Critical Review of Theories and Evidence - Zheng, Ya; Yang, Zhong; Jin, Chunlan; Qi, Yue; Liu, Xun (Frontiers in Psychology, 2017)
Fairness-related decision making is an important issue in the field of decision making. Traditional theories emphasize the roles of inequity aversion and reciprocity, whereas recent research increasingly shows that emotion plays a critical role in this type of decision making. In this review, we summarize the influences of three types of emotions (i.e., the integral emotion experienced at the time of decision making, the incidental emotion aroused by a task-unrelated dispositional or situational source, and the interaction of emotion and cognition) on fairness-related decision making. Specifically, we first introduce three dominant theories that describe how emotion may influence fairness-related decision making (i.e., the wounded pride/spite model, affect infusion model, and dual-process model). Next, we collect behavioral and neural evidence for and against these theories. Finally, we propose that future research on fairness-related decision making should focus on inducing incidental social emotion, avoiding irrelevant emotion when regulating, exploring the individual differences in emotional dispositions, and strengthening the ecological validity of the paradigm.